2007
DOI: 10.1177/0961203306073135
|View full text |Cite
|
Sign up to set email alerts
|

Fine specificity of the Ro/SSA autoantibody response in relation to serological and clinical findings in 96 patients with self-reported cutaneous symptoms induced by the sun

Abstract: Anti-Ro/SSA assays assist the clinician in distinguishing autoimmune diseases such as Sjögrenś syndrome (SS), systemic lupus erythematosus (SLE) and subacute cutaneous lupus erythematosus (SCLE). The objective of the study was to investigate the fine specificity of the autoantibodies in relation to clinical presentation as well as environmental and endogenous factors such as photosensitivity, smoking and immunoglobulin (Ig) levels in patients with Ro/SSA autoantibodies. Serum samples from 96 anti-Ro/SSA positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 36 publications
(51 reference statements)
2
24
1
Order By: Relevance
“…Accordingly, another study noted twice as many non-smokers with SLE than smokers in their study population. 14 We have shown with logistic regression modelling that smoking was not associated with the involvement of internal organs in our LE patients. McAlindon et al also found that smoking was not related to the development of lupus nephritis in SLE.…”
Section: Does Smoking Behavior Differ In Cutaneous Variants Of Le?mentioning
confidence: 93%
“…Accordingly, another study noted twice as many non-smokers with SLE than smokers in their study population. 14 We have shown with logistic regression modelling that smoking was not associated with the involvement of internal organs in our LE patients. McAlindon et al also found that smoking was not related to the development of lupus nephritis in SLE.…”
Section: Does Smoking Behavior Differ In Cutaneous Variants Of Le?mentioning
confidence: 93%
“…Finnish (n = 101) and Swedish (n = 134) patients positive for Ro/SSA-autoantibodies were first analysed individually and further in combination (n = 235) as a pooled dataset in order to study the association between ITGAM and immunological factors [12], [26]. Ro-autoantibodies were selected for detailed investigation, because they may have pathobiological importance in apoptosis and phagocytosis [27] similarly to ITGAM , and prognostic value for predicting systemic inflammatory disease [28]. Furthermore, several genetic regions harbouring genes for adhesion molecules have shown evidence of association to DLE in the presence of Ro-autoantibodies [6] and the disease progression may be highly dynamic in Ro-positive patients [29].…”
Section: Methodsmentioning
confidence: 99%
“…SSA/Ro52 is a newly characterized RING-finger-type E3 ubiquitin ligase (Espinosa et al 2006;Wada and Kamitani 2006), which in unstimulated cells localizes to the cytoplasm (Ohlsson et al 2002). Autoantibodies against SSA/Ro52 are commonly found in patients with SLE (Hassan et al 2002;Hoffman et al 2004;Popovic et al 2007;Routsias et al 2006). Interestingly, SSA/Ro52 redistributes itself to apoptotic blebs in cardiac monocytes, epithelial cells, salivary gland cells and keratinocytes after exposure to various pro-apoptotic agents (Igarashi et al 1995;McArthur et al 2002;Miranda et al 1998;Ohlsson et al 2002).…”
Section: Introductionmentioning
confidence: 99%